Applying the McKinsey 7S Model for Achieving Sustainable Performance Management at CV Fresh Bright Pool Tanjungpinang - Billal Alrexa; Cavin Rahadian; Muhammad Angga N; Risnai Langgeng; Satriadi (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This research aims to analyze the application of the McKinsey 7S framework in achieving sustainable performance management at Fresh Bright Pool, Tanjungpinang, amid the increasingly competitive local entertainment industry. The study explores the seven core elements of McKinsey 7S—strategy, structure, systems, shared values, skills, leadership style, and staff—to understand the dynamics of performance management and innovation in the service sector. A qualitative approach was employed, collecting data through in-depth interviews with two staff members and several visitors, supported by document analysis to ensure data validity. The results show that the elements of strategy and shared values are the primary strengths of Fresh Bright Pool in creating superior customer experiences, such as through the improvement of billiard facilities, optimization of bar services, and implementation of a more structured reservation system. The shared value of "comfort and togetherness" has successfully built a friendly and inclusive work culture. Collaborative leadership styles enhance staff engagement in operational processes, while the skills and staff elements still face challenges, including limited technical training and capacity development in customer service. This study provides valuable insights for Fresh Bright Pool to continue strengthening these elements to improve efficiency, maintain competitive advantage, and achieve operational sustainability in the local entertainment industry.